Informal Land Titles: Snowden v Baker (1844) - Kercher, Bruce (Victoria University of Wellington Law Review, 2010)
Snowden v Baker (1844) concerned the judicial recognition of informal land titles. This article compares the treatment of this broad question in Newfoundland and New South Wales, with Snowden v Baker. In Newfoundland and New South Wales, informal titles gained legal recognition. This happened in Newfoundland through judicial creativity, including statutory interpretation. In New South Wales, the formal law was applied more strictly, but was softened when commissioners were appointed to assess whether Crown discretion should be exercised in favour of those dispossessed due to informality. Both methods were used in New Zealand, where the informal titles of British settlers derived from sales by Māori land owners. Titles purchased from Māori owners were declared null and void unless based on Crown grants. As in New South Wales, commissioners were appointed to advise whether such grants should be made. In Snowden v Baker, Martin CJ used statutory interpretation to take a further step, by holding that titles derived from Māori sales had a contingent validity until affirmed or denied by the Crown.